Measurement of the rotational inertia of bodies by using mechanical spectroscopy - Fonzar Pintao, Carlos Alberto (Korean Soc Mechanical Engineers, 2014)
In this paper, mechanical spectroscopy was used to study the rotational inertia of bodies. In order to verify and show its importance in relation to other techniques, measurements of the internal friction and rotational inertia of a body with liquid or sand inside were carried out. For a solid without axes and planes of symmetry, properties such as the matrix, directions and principal moments of inertia, variation of the rotational inertia for each of the coordinate planes, and the ellipsoid of inertia were determined. Force sensors and rotational motion were used in the measurements taken in an arrangement that was specifically designed for this type of measure.
Keywords: Anelastic relaxation theory; Rotational inertia; Inertia ellipsoid; Moment of inertia